2017
DOI: 10.1007/s11103-017-0610-z
|View full text |Cite
|
Sign up to set email alerts
|

CBF2A–CBF4B genomic region copy numbers alongside the circadian clock play key regulatory mechanisms driving expression of FR-H2 CBFs

Abstract: The C-Repeat Binding Factors (CBFs) are DNA-binding transcriptional activators that were identified using Arabidopsis thaliana. In barley, Hordeum vulgare, a cluster of CBF genes reside at FROST RESISTANCE-H2, one of two loci having major effects on winter-hardiness. FR-H2 was revealed in a population derived from the winter barley 'Nure' and the spring barley 'Trèmois'. 'Nure' harbors two to three copies of CBF2A and CBF4B as a consequence of tandem iteration of the genomic region encompassing these genes whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(36 citation statements)
references
References 52 publications
(80 reference statements)
0
35
0
1
Order By: Relevance
“…In the present study, no evident correlation between CNV and expression level for HvCBF4 and HvCBF2A genes was observed after the cold treatment in dark conditions. Conversely, Dhillon et al [18] reported the association between HvCBF4-HvCBF2A copy numbers and HvCBF2 transcript levels; however, in their experiment plants were subjected to light and cold temperature (6°C) stimuli at the same time. Consequently, this implies that the observed expression was the sum/interaction of both environmental factors, each influencing HvCBF expression.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In the present study, no evident correlation between CNV and expression level for HvCBF4 and HvCBF2A genes was observed after the cold treatment in dark conditions. Conversely, Dhillon et al [18] reported the association between HvCBF4-HvCBF2A copy numbers and HvCBF2 transcript levels; however, in their experiment plants were subjected to light and cold temperature (6°C) stimuli at the same time. Consequently, this implies that the observed expression was the sum/interaction of both environmental factors, each influencing HvCBF expression.…”
Section: Discussionmentioning
confidence: 96%
“…The regulation also involves members of the calmodulin-binding transcription activator (CAMTA) family and the activation of phytochromes, which play an important role in light-mediated stimulus. Moreover, under warm temperatures, CBFs expression is regulated by the circadian clock through the action of a central oscillator (namely CCA1 and LHY), and day length (photoperiod) [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, phylogenetic reconstruction supports the early recruitment of VRN1 in vernalization responsiveness, at least in the ancestor of all Pooideae tribes minus Nardeae and Brachyelytreae, but not before the diversification of Pooideae from Bambusoideae (McKeown et al ., ). An additional possible connection between short‐ and long‐term cold responses could be through changes in circadian clock regulation, which are widely known to have large effects on cold responses and flowering time regulation (Salomé & McClung, ; Yamashino et al ., ; Nakamichi et al ., ; Dong et al ., ; Chow et al ., ; Greenham & McClung, ; Seo & Mas, ; Dhillon et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The genetics of vernalization‐mediated flowering and cold acclimation has been largely elucidated in distantly related model species, each being regulated by a number of genes that form complex, and likely interconnected, networks (Thomashow, ; Yan et al ., , , ; Deng et al ., ; Kippes et al ., ; Zhao et al ., ; Dhillon et al ., ). Specifically, vernalization responsiveness in cereal grasses such as barley and wheat (Pooideae) is controlled by at least three core interacting proteins, VERNALIZATION1 (VRN1), VRN2 and VRN3 (Yan et al ., , , ; Kippes et al ., ).…”
Section: Introductionmentioning
confidence: 97%